High-flow nasal cannula versus continuous positive airway pressure in primary respiratory support for preterm infants: A systematic review and meta-analysis - Luo, Keren; Huang, Yi; Xiong, Tao; Tang, Jun (Frontiers in Pediatrics, 2022)
Respiratory support is crucial for the survival of preterm infants, and High-flow Nasal Cannula Oxygen Therapy (HFNC) and Continuous Positive Airway Pressure (CPAP) are commonly used for neonatal respiratory support. This meta-analysis aimed to compare the effects of HFNC and CPAP in primary respiratory support for preterm infants, to provide evidence-based support for clinical practice. PubMed, Embase, Cochrane Library, ClinicalTrials.gov, CNKI, VIP, WANFANG and SinoMed were searched for eligible studies. The primary outcomes included the incidence of treatment failure and the application of mechanical ventilation. A total of 27 eligible studies with 3,351 participants were included. There was no significant difference in the incidence of respiratory support failure [RR = 1.17, 95%CI (0.88–1.56)] and the application of mechanical ventilation [RR = 1.00, 95%CI (0.84–1.19)] between HFNC group and CPAP group. HFNC resulted in lower rate of air leaks [RR = 0.65, 95%CI (0.46–0.92)], nasal trauma [RR = 0.36, 95%CI (0.29–0.45)] and abdominal distension [RR = 0.39, 95%CI (0.27–0.58)], and later time of mechanical ventilation initiating [SMD = 0.60, 95%CI (0.21–0.99)], less duration of oxygen therapy [SMD = −0.35, 95%CI (−0.68 to −0.02)] and earlier enteral feeding [SMD = −0.54, 95%CI (−0.95 to −0.13)]. Alternative non-invasive respiratory support after initial treatment failure resulted in no difference in the application of mechanical ventilation between the two groups [RR = 0.99, 95%CI (0.52–1.88)]. HFNC might be more effective and safer in primary respiratory support for preterm infants. Using CPAP as a remedy for the treatment failure of HFNC could not avoid intubation. For premature infants with the gestational age <28 weeks, HFNC as primary respiratory support still needs to be further elucidated. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022313479, identifier: CRD42022313479.